2017
DOI: 10.1371/journal.pone.0178609
|View full text |Cite
|
Sign up to set email alerts
|

Acizzia solanicola (Hemiptera: Psyllidae) probing behaviour on two Solanum spp. and implications for possible pathogen spread

Abstract: Piercing-sucking insects are vectors of plant pathogens, and an understanding of their feeding behaviour is crucial for studies on insect population dynamics and pathogen spread. This study examines probing behaviour of the eggplant psyllid, Acizzia solanicola (Hemiptera: Psyllidae), using the electrical penetration graph (EPG) technique, on two widespread and common hosts: eggplant (Solanum melongena) and tobacco bush (S. mauritianum). Six EPG waveforms were observed: waveform NP (non-probing phase), waveform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
1
0
3
Order By: Relevance
“…Liberibacter spp.-infected psyllids (Sandanayaka et al 2014;Killiny et al 2017), whereas our study found a decrease in xylem ingestion similar to (Antolinez et al 2017a, b). Possible explanations for the observed differences could be osmotic stresses (Pompon et al 2011), host plant health (Cen et al 2012), host mechanical/chemical stimuli (Valenzuela et al 2017) and plant age (Luo et al 2015a, b) to mention a few. Our study did not test specific reasons why the feeding behaviour of infected psyllids was different to non-infected ones and to results from some previous studies.…”
Section: Probing Behaviour Of Clso-infected and Non-infected B Cockementioning
confidence: 99%
“…Liberibacter spp.-infected psyllids (Sandanayaka et al 2014;Killiny et al 2017), whereas our study found a decrease in xylem ingestion similar to (Antolinez et al 2017a, b). Possible explanations for the observed differences could be osmotic stresses (Pompon et al 2011), host plant health (Cen et al 2012), host mechanical/chemical stimuli (Valenzuela et al 2017) and plant age (Luo et al 2015a, b) to mention a few. Our study did not test specific reasons why the feeding behaviour of infected psyllids was different to non-infected ones and to results from some previous studies.…”
Section: Probing Behaviour Of Clso-infected and Non-infected B Cockementioning
confidence: 99%
“…Os dados foram analizados utilizando o software Stylet+ para Windows (EPG Systems, Wageningen, Holanda) (Tjallingii, 1978(Tjallingii, , 1988. As formas de ondas de EPG foram Assim como os estudos conduzidos por Valenzuela et al (2017), no presente trabalho não foi incluída a marcação da onda Z, relacionada a atividades de caminhamento (Youn et al, 2011), nem das ondas A e B, relacionadas a penetração inicial do estilete e a salivação na epiderme/mesófilo (Cen et al, 2012), sendo a onda Z parte de nossa marcação de onda NP e as ondas A e B partes de nossa marcação de C. Além disso, os registros foram analisados do início ao fim e incluíram a última onda interrompida não naturalmente pelo fim das 8 h de registro.…”
Section: Análise Dos Registros De Epgunclassified
“…L. brunswickensis' na Australia. A. solanicola também tem sido investigada como um potencial vetor de CaLsol(Valenzuela et al, 2017).No presente levantamento, que foi realizado com diferentes métodos de amostragem em várias áreas produtoras de olerícolas no Brasil, nenhuma das espécies exóticas e já conhecidas como vetores de CaLsol foi observada. Entretanto, foram constatadas diversas espécies de psilídeos pertencentes a 20 gêneros, com destaque para R. solanicola, R. capsici e I. foram representadas por algum exemplar deste trabalho.…”
unclassified
See 1 more Smart Citation